2002
DOI: 10.1007/s00268-002-6620-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Intraoperative Quick Parathyroid Hormone Assay Improve the Results of Parathyroidectomy?

Abstract: Preoperative sestamibi (MIBI) and ultrasonography (US) are used to localize parathyroid tumors in patients with primary hyperparathyroidism (pHPT). The intraoperative quick PTH assay (qPTH) has been recommended to determine whether all hyperfunctioning parathyroid tissue has been removed. We questioned whether qPTH improves the results of parathyroidectomy in patients with pHPT. We analyzed 115 unselected patients with pHPT without a family history or multiple endocrine neoplasia but who had undergone parathyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 14 publications
2
85
1
5
Order By: Relevance
“…Fortunately, we could successfully remove hyperactive gland by excising single gland in the present series in most of the patients. It was reported that when surgeon-performed US showed positive or typical localization of at least one gland, MIP with IOPM could improve the result [19,20]. Although we could not determine the significance of IOPM in the present series, we might be able to prevent 2 bilateral explorations by employing IOPM.…”
Section: Discussionmentioning
confidence: 39%
“…Fortunately, we could successfully remove hyperactive gland by excising single gland in the present series in most of the patients. It was reported that when surgeon-performed US showed positive or typical localization of at least one gland, MIP with IOPM could improve the result [19,20]. Although we could not determine the significance of IOPM in the present series, we might be able to prevent 2 bilateral explorations by employing IOPM.…”
Section: Discussionmentioning
confidence: 39%
“…28 Sestamibi scanning has a high positive predictive value, but is more accurate for single gland rather than multigland disease. [29][30][31][32] High resolution ultrasound scanning alone is less accurate than sestamibi scanning, but used in combination the accuracy of detection improves, [33][34][35] especially for single gland disease. 29 There is a false negative rate of up to 22% with sestamibi scans in primary hyperparathyroidism; this is more likely with small adenomas, multigland disease, superior glands, or normal preoperative calcium concentrations.…”
Section: Will the Parathyroid Frozen Section Soon Be Left Out In The mentioning
confidence: 99%
“…IOPTH measurement has a reported sensitivity of 58% in detecting further adenomas in cases of multiple gland disease. 14 This relatively low figure suggests that while IOPTH is helpful in confirming single gland disease, it does not offer complete protection against missing additional abnormal glands. IOPTH measurement may produce both false positive and false negative results.…”
Section: Discussionmentioning
confidence: 97%